The Effect of Leverage, Company Size, Capital Intensity on Tax Avoidance with Profitability as Moderating Variable - Tri Surya Ambar Wati; Andrea Ivy Mintjelungan; Vinola Herawaty (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study examines the effect of leverage, company size, and capital intensity on tax avoidance, with profitability as a moderating variable. It addresses direct effects of leverage, firm size, capital intensity, and profitability on tax avoidance, as well as the moderating role of profitability in these relationships. Using a quantitative approach, the study analyzes companies listed on the Indonesia Stock Exchange through multiple regression and moderation testing. The results show that leverage and capital intensity do not significantly affect tax avoidance, indicating that debt levels and fixed asset proportions are not dominant factors influencing corporate tax avoidance behavior. In contrast, firm size has a significant negative effect, suggesting that larger companies tend to engage less in tax avoidance due to stronger regulatory supervision and reputational considerations. Profitability does not significantly moderate the relationship between leverage or capital intensity and tax avoidance. However, profitability significantly moderates the relationship between firm size and tax avoidance, indicating that more profitable large firms are associated with lower tax avoidance tendencies. These findings imply that structural factors alone may not determine tax avoidance, while the interaction between firm size and profitability plays an important role in shaping corporate tax behavior and governance.